Imperative for the Future Human Happiness (Project of Volodymyr Vynnychenko) - Nataliia Zhukova (International Society of Philosophy and Cosmology, 2019)
The article is devoted to the moral reflections of Volodymyr Vynnychenko (1880-1951), a Ukrainian writer, playwright, first prime minister, a staunch supporter of political freedom of the Ukrainian state. Vynnychenko's moral searches are basedon the actualization of spiritual love,erotic and sexual relationships as a problem of happiness, self-improvement as the means of activating the moral principle of "honesty with oneself," as well as the pursuit of social justice, which in general provide the exactbalance and harmony the writer so sought to achieve, connect a person with other people, while maintaining at the same time one's freedom and individuality. The logic of forming a moral conceptcompares the ideas of "concordism" by Volodymyr Vynnychenko and Albert Schweitzer's (1875-1965) concept of "reverence for life." Arguably, unlike Vynnychenko, Schweitzer sought the highest philosophical truth, first of all, to turn it into realityhimself, to achieve a spiritual connection with the Universethrough the ethics of reverence for life. For Schweitzer, to become moral means to become truly thinking, to do good for the afflicted is an internal need, the leitmotif of his whole life